LEARNING ORGANIZATION DISCIPLINE IN DEVELOPING EMPLOYEES’ PERFORMANCE OF DRINGKING WATER REGIONAL COMPANY OF SINJAI REGENCY - Yudarti; Mursak; Darmawati (Program Studi Administrasi Publik, 2022)
Learning Organization is an organization that creates an atmosphere of support and provide thewidest opportunity for individuals in it to learn individually and in group, and to apply the results of his study into the processes and activities of the organization. The aim of this study was to analyze the whether there was a Learning Organization has been applied to the Regional Water Company (PDAM) Sinjai, but it also wants to know whether learning organization can improve the performance of employees at the Regional Water Company (PDAM) Sinjai. This study was carried out in the Regional Water Company (PDAM) Sinjai. This study used qualitative research approach. Qualitative research methodology is a process, principles and procedures to approach the problem and look for answers. Data collection techniques were indepth and open interview techniques, observation, direct observation and reviews of written documents. Result of this research indicate that Basically Company of Drinking Water Area ( PDAM) of Regency Sinjai Not yet entered the organization category which Learning. But do conduct an effort to remain to to give the prima service to all cutomer client with as effective as possible and also do conduct the effort of so that to be remain to able to hold out and vie with the other company. Others with the discipline learn which is in applied at Company of Drinking Water Area (PDAM) of Regency Sinjai, can improve the Employees performance although not yet too effective because there be still hisits is problem which emerge among employees humanity in this case still not yet sinergi.